Lessons for sustainability from the world's most sustainable culture - Wills-Johnson, Nick (Centre for Research in Applied Economics (CRAE), Curtin Business School, 2009)
Sustainable development is one of the key challenges faced by societies today. Yet it is not a new challenge; throughout history, societies have faced the need to live within environmental constraints. Some have done so well, and some poorly. One society which did well for tens of thousands of years is that of Aboriginal Australia. This paper explores some lessons from Aboriginal Australia which have resonance in the modern world and shows that countries which have learned those lessons are in fact more sustainable than those which have not. It thus suggests that there is much that the pantheon of human experience can teach the modern world as it endeavours to create a sustainable future.